Basal and Calcium-Stimulated Procalcitonin for the Diagnosis of Medullary Thyroid Cancers: Lights and Shadows - Censi, Simona; Di Stefano, Marta; Repaci, Andrea; Benvenuti, Teresa; Manso, Jacopo; Pagotto, Uberto; Iacobone, Maurizio; Barollo, Susi; Bertazza, Loris; Galuppini, Francesca; Benna, Clara; Pennelli, Gianmaria; et al. (Frontiers in Endocrinology, 2021)
Background Procalcitonin (proCt) was recently proposed as an alternative or in addition to calcitonin (Ct) in medullary thyroid cancer (MTC) diagnostics. Methods Serum basal Ct (bCt) and proCt (bproCt) levels were measured before surgery from a consecutive series of patients with (n=43) and without (n=75) MTC, retrospectively collected in Padua. Serum bproCt, bCt and stimulated proCt and Ct (sproCt and sCt) were measured in another consecutive series of 33 patients seen at three tertiary-level institutions undergoing a calcium stimulation test prior to surgery, 20 of them with a final diagnosis of MTC, and 13 with non-MTC nodular disease. Results Median bproCt levels were higher in MTC than in non-MTC. A positive correlation was found for bproCt with bCt (P<0.01, R2 = 0.75), and with tumor size (P<0.01, R2 = 0.39). The cut-off for bproCt differentiating between MTC and non-MTC patients was >0.07 ng/ml (sensitivity: 85.7%, specificity: 98.9%, positive predictive value [PPV]: 98.2%, negative predictive value [NPV]: 90.6%, P<0.01). While bproCt was >0.07 ng/ml in 38/39 (97.4%) patients with MTC >10 mm, it was above said cut-off only in 15/23 (65.2%) patients with tumors ≤10 mm. A sproCt >0.19 ng/ml was able to identify MTC [sensitivity: 90.0%, specificity:100.0%, PPV: 100.0%, NPV: 86.7% (P<0.01)]. Conclusions Our data suggest that bproCt can be a good adjunct to Ct for MTC diagnostic purposes. In consideration of its high specificity, it can be used in combination with Ct in MTC diagnostics, particularly in the case of mildly elevated basal Ct levels.